Improving the Students’ Creativity in Writing Descriptive Texts by Using Super PC Media - Lailatul Musyarofah; Amaliah Amaliah (STKIP PGRI SIDOARJO, 2019)
The purpose of this study was to describe the increase of students’ creativity in writing descriptive text by using Super PC with mind map method. The result of this study wasthe students’ creativity could be developed by means of creative teachers who also contextualized learning with media that students have known every day, that is by using super PC (Supermarket Product Catalog) media. The use of Super PC media in the seventh grade of Junior High School 2 Sidoarjo brings a positive impact to the students’ creativity in writing descriptive text. This can be seen from the comparison of Cycle I, that is, with index 2.26, with less creative category. Whereas in the second cycle (Cycle II), the index was improving to 4.45 with a very creative category. Students have a creative character and in terms of practicality, clarity, quality and usefulness. The results of writing gradually improve positively. This media is also specifically designed to overcome saturation, limited vocabulary in using international language in the implementation of learning that prepares students in the 21st century, especially students’ creativity in writing descriptive text.